PET-CT in the-subarctic region of Norway 2010-2013. At the edge of what is possible? - Norum, Jan; Søndergaard, Ursula; Traasdahl, Erik; Nieder, Carsten; Tollåli, Geir; Andersen, Gry; Sundset, Rune (BMC Medical Imaging, 2015)
Published version. Source at http://doi.org/10.1186/s12880-015-0073-0 . Background It is challenging to obtain a similar access to positron emission tomography/computed tomography (PET-CT) within the whole region served. In the subarctic and arctic region of Norway, significant distances, weather conditions and seasonable darkness have been challenging when the health care provider has aimed for a high quality PET-CT service with similar availability to all inhabitants. Methods The PET-CT service at the University Hospital of North Norway (UNN) was established in May 2010. The glucose analogue tracer fluorine-18 fluorodeoxyglucose (FDG) was delivered from Helsinki, Finland. An ambulatory PET-CT scanner was initially employed and a permanent local one was introduced in October 2011. In March 2014, we analysed retrospectively all data on the PET-CT exams performed at the Section of Nuclear Medicine, Department of Radiology during a 32 months time period 2010–13. The following patient data were recorded: gender, age, diagnosis, residence and distance of travelling. There were in total 796 exams in 706 patients. Results Four hundred sixty-one PET-CT exams per million inhabitants were, on average, performed per year. Lung cancer (32.7 %), malignant melanoma (11.3 %), colorectal cancer (10.9 %) and lymphoma (9.7 %) constituted two-thirds of all exams. Three-fourths were males and the median age was 63.5 years (range 15.2–91.4 years). The access to PET-CT exam varied within the region. The southern county (Nordland) experienced a significantly less access (p < 0.0001) to the regional service. Except for malignant melanoma, this finding was observed in all major cancer subgroups. In colorectal cancer and lymphoma a lower consumption of PET-CT was also observed in the northeastern county (Finnmark). Patients’ mean distance of travelling by car (one way) was 373 km (median 313 km, range 5–936 km). Conclusion PET-CT was not similarly available within the region. Especially, inhabitants in the southern county ...